Orofacial anti-hypernociceptive effect of citral in acute and persistent inflammatory models in rats - Santos, Bruna M.; Santos, Wanderson S.; Solon, Isabelly G.; Garcia, Felipe S.; Emilio Silva, Maycon Tavares [UNESP]; Jesus, Aline A.; Hiruma-Lima, Clélia Akiko [UNESP]; Nascimento, Glauce C.; Cárnio, Evelin C.; Branco, Luiz G.S. (Elsevier, 2023)
Orofacial pain has significant psychological and physiological effects. Citral (3,7-dimethyl-2,6-octadienal) is the main component of Cymbopogon citratus (DC) Stapf, an herb with analgesic properties. Although citral has been considered a potent analgesic, its putative effects on orofacial pain are still unknown. Objective: The objective of this study is to test the hypothesis that citral modulates orofacial pain using two experimental models: formalin-induced hyperalgesia in the vibrissae area and during persistent temporomandibular hypernociception using Complete Freund's Adjuvant - CFA test. Methods: For the formalin test, citral (100 and 300 mg/kg, oral gavage) or its vehicle (Tween 80, 1 %) were given 1 h before the formalin injection subcutaneously (sc) into the vibrissae area. For the CFA model, we analyzed the prophylactic (100 mg/kg of citral by oral gavage, 1 h before CFA injection) and the chronic therapeutic (citral treatment 1-hour post-CFA injection and daily post-CFA injection) effect of citral or its vehicle in animals treated with CFA for 8 days. Results: Citral caused a decrease in formalin-induced local inflammation and the time spent performing nociceptive behavior in a dose-dependent fashion. Similarly, prophylactic and therapeutic citral treatment decreased the CFA-induced persistent mechanical hypernociception in the temporomandibular area. Conclusion: Our data strengthen the notion that citral plays a powerful antinociceptive role by decreasing orofacial hypernociception in formalin and CFA models.
Keywords: Complete Freund's Adjuvant; Formalin; Inflammation; Orofacial pain; Temporomandibular disorders; Trigeminal system